A new stingless bee species of the genus Scaura (Hymenoptera, Apidae) from the Brazilian Atlantic forest, with notes on S. latitarsis (Friese) - Melo, Gabriel A.r.; Costa, Marco Antônio (Zootaxa, 2004)
A new species, Scaura atlantica Melo, is described from eastern Brazil. It belongs to the latitarsis group and can be distinguished from workers of S. latitarsis especially by its larger body size, darker color, smoother upper frons, and by the contour of the posterior margin of the hind basitarsus; from workers of S. argyrea, n. stat., it differs by possessing a frons with shorter simple setae whose sockets are less protuberant, shorter simple setae on the mesoscutum and by the shape of the hind basitarsus. Considering that the original type series of Trigona latitarsis Friese, 1900, is probably composed of more than one species, a worker syntype from Brazil (Jundia , S o Paulo) is here designated lectotype in order to stabilize the taxonomy of the group.